DINAMIKA SOSIAL DAN POLA KOMUNIKASI VIRTUAL KOMUNITAS GAME ONLINE : (STUDI NETNOGRAFI GRUP FACEBOOK AQ3D INDONESIA) - Arya Yusuf Alwafi; Zikri Fachrul Nurhadi; Haryadi Mujianto (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
The advancement of digital technology has given rise to various online communities, including gaming communities that serve as new spaces for social interaction. This study aims to examine the social dynamics and patterns of virtual interaction within the AQ3D Indonesia community, which operates through the Facebook platform. A qualitative method with a netnographic approach was used, involving online observation, interviews with community members, and digital content analysis. The findings indicate that the community functions not only as a space for sharing technical gaming information but also as a site for forming collective culture, solidarity, and strong digital social identity. Interactions occur through strategy discussions, sharing personal experiences, and showing empathy among members, both within and beyond the context of gaming. These findings highlight that online gaming communities can serve as meaningful social spaces that foster interpersonal connections in the digital age.